Economic and social implications of low-emission development pathways in Brazil. Issue 5 (3rd September 2018) - La Rovere, Emilio L.; Wills, William; Grottera, Carolina; Dubeux, Carolina B. S.; Gesteira, Claudio
Abstract: As one of the largest developing economies in the world, Brazil faces huge challenges apart from climate change, such as poverty eradication, reducing inequalities, ensuring food and energy security, social coverage, technological innovation and industrial competitiveness. This paper summarizes an analysis of the social and economic implications of long-term greenhouse gas emissions scenarios in Brazil. Recent studies analyzing low-carbon scenarios for Brazil are reviewed, including the IES-Brasil (Economic and Social Implications of Mitigation Scenarios in Brazil) scenarios up to 2030 and 2050, the latter including an emissions pathway consistent with a 1.5 °C target for limiting global temperature increase. The findings of these studies highlight that, if appropriate policy tools (both command-and-control measures and microeconomic policies) are used to overcome the barriers to mitigation options, a decoupling of economic growth and GHG emissions would be possible without harming economic and social development in Brazil.